(untitled) (International Seven Journal of Multidisciplinary, 2025)
This article addresses the inclusion of children with Autism Spectrum Disorder (ASD) in Early Childhood Education, considering the different pathways and approaches that foster this process in the school environment. The main objective was to reflect on the pedagogical, structural, and formative aspects that directly impact the quality of inclusion and the comprehensive development of children with ASD. To this end, we adopted a qualitative bibliographical research methodology, based on recent works, scientific articles, and official documents addressing school inclusion, teaching practices, public education policies, and inclusive pedagogical practices focused on early childhood. Analysis of the material revealed that the inclusion of autistic children requires more than physical and curricular adaptations; it demands an ethical commitment to diversity, solid and ongoing teacher training, and the development of a welcoming and collaborative school culture. Active listening, sensitive mediation, flexible planning, the use of visual resources, and the presence of support networks were found to be fundamental elements in ensuring the effective participation of students with ASD in school activities. The importance of collaboration between families, schools, and multidisciplinary teams was also noted in promoting strategies that respect the specificities and potential of each child. The analysis concludes that inclusion, when implemented with intentionality, sensitivity, and collective responsibility, contributes to building a more just, democratic, and meaningful school for all involved. By recognizing the unique characteristics of children with ASD and ensuring their protagonism in the daily school routine, Early Childhood Education strengthens its social function of embracing diversity and promoting full development from the earliest years of life.